Pentingnya Keseimbangan Unsur Cipta, Rasa, dan Karsa dalam Proses Pengembangan Potensi Diri (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
The balance between cipta, rasa and karsa is a fundamental concept in human beings. These three elements are terms proposed by Ki Hajar Dewantara known as the “Konsep Trisakti Jiwa”, namely: cipta, rasa, and karsa which are also known as reasoning, appreciation, and practice. What is meant in the concept is that in carrying out everything there must be a synergistic combination between the results of thought (cipta), the results of taste (rasa), and strong motivation within themselves (karsa). This concept emphasizes the importance of balancing these three aspects to form individual character and creativity. This research aims to provide information on what can be done to balance the three aspects of cipta, rasa, and karsa; and how important the balance of cipta, rasa, and karsa is in the process of developing one's potential. Through a literature review, this research analyzes several journals from the Google Scholar website, papers, books and so on that are in accordance with the topic being discussed. The results show that someone who can unleash all the potential within themselves does not solely focus on developing intellectual abilities, but they also continue to train to increase emotional awareness, and also motivate themselves to move forward. If in carrying out everything only relies on one of them, it is likely that it will be far to reach the goal. By balancing these three aspects of creation, taste, and karsa, individuals can increase self-awareness, so that this can make it easier for an individual to explore and develop their existing potential.